TINJAUAN PROGRAM MAGANG KAMPUS MERDEKA DALAM ASPEK HUKUM KETENAGAKERJAAN - Elgi Hikmat Syah; Taun Taun (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2023)
The internship program currently implemented in Indonesia has several types of internships, some are intended for job seekers or job training, for academic purposes, or internships to meet certain professional requirements. The Merdeka Campus Internship is carried out as an effort to prepare students to face the changes that occur, including cultural, social, world of work aspects, and rapid technological advances, from the program the competencies of students need to be prepared as an effort to integrate abilities with the needs of the world of work market and industry (link and match). The purpose of this paper is to find out the legal position of the students of the Independent Campus interns and the legal protection of the trainees is reviewed in the aspects of labor law. The approach taken in this writing is the statue approach; conceptual approach; and analytical approach. The results of this paper found that there was a problem where the Merdeka Campus Internship program did not have a firm and strong legal basis for the implementation of internships carried out by students, there were problems with the occurrence of legal vacancies making the MBKM program less legally certain. The legal protection of independent campus internship participants is based on the provisions contained in the MSIB Brief Guide and the good faith of IDUKA Partners, as for if there is a violation, students can report it to the Ministry of Education and Culture and the authoritiesAbstrakProgram pemagangan yang saat ini dilaksanakan di Indonesia memiliki beberapa jenis pemagangan, ada yang ditujukan untuk para pencari kerja atau pelatihan kerja, untuk tujuan akademis, maupun magang untuk memenuhi syarat profesi tertentu. Adapun Magang Kampus Merdeka dijalankan sebagai upaya menyiapkan mahasiswa dalam menghadapi perubahan yang terjadi, meliputi aspek budaya, sosial, dunia kerja, dan pesatnya kemajuan teknologi, dari program tersebut kompetensi dari mahasiswa perlu disiapkan sebagai upaya mengintegrasikan kemampuan dengan kebutuhan pasar dunia kerja dan industri (link and match). Tujuan dari penulisan ini adalah untuk mengetahui kedudukan hukum mahasiswa peserta magang Kampus Merdeka dan perlindungan hukum peserta pemagangan ditinjau dalam aspek hukum ketenagakerjaan. Pendekatan yang dilakukan dalam penulisan ini adalah statue approach; conceptual approach; dan analytical approach. Hasil dari penulisan ini menemukan bahwa terdapat problematika dimana program Magang Kampus Merdeka belum memiliki dasar hukum yang tegas dan kuat atas pelaksanaan magang yang dilakukan mahasiswa, terdapat permasalahan dengan terjadinya kekosongan hukum menjadikan program MBKM kurang akan kepastian secara hukum. Perlindungan hukum peserta Magang Kampus Merdeka didasarkan pada ketentuan yang termuat pada Panduan Singkat MSIB serta itikad baik dari Mitra IDUKA, adapun bila terdapat pelanggaran maka mahasiswa dapat melaporkannya kepada Kemendikbudristek maupun pihak berwajib